Psikoterapi Pemberdayaan: Berbagi Tiga Hal Baik untuk Mengatasi Burnout Perawat di Era COVID-19 - Sri Nining; Rr. Tutik Sri Hariyati; La Ode Abdul Rahman; Lilis Rayatin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify problems and determine improvement strategies to overcome burnout nurses. The research method used is a case report to assess quality improvement with an 8-step approach to change starting from problems with observation and screening of burnout using the Maslach Burnout Inventory Human Services Survey (MBI-HSS), analysis using a fishbone approach, determining improvement strategies, implementing and program evaluation. The results showed that 55% of nurses experienced a decrease in self-esteem, but through the Empowerment Psychotherapy program: Three Good Things, which was carried out for two weeks, it was able to reduce the burnout level of nurses as assessed by the Mini Z burnout survey. In conclusion, Empowerment Psychotherapy: Three Good Things can overcome nurse burnout problems. It is recommended that the implementation of this program be carried out thoroughly in all work units. Keywords: Burnout Management, Nurses, Empowerment Psychotherapy, Three Good Things